2008
DOI: 10.1182/blood-2007-05-092486
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of CD49d protein expression as overall survival and progressive disease prognosticator in chronic lymphocytic leukemia

Abstract: CD49d/␣4-integrin is variably expressed in chronic lymphocytic leukemia (CLL

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

30
213
4
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 218 publications
(257 citation statements)
references
References 57 publications
(109 reference statements)
30
213
4
2
Order By: Relevance
“…The optimal cut off for CD69 expression yielding the best separation of CLL patients into 2 subsets with significantly different prognosis was fixed at 30% of positive cells by applying the most commonly used methods. 9,13,32,34 Since our proposal is to use CD69 for prognostic purposes, we confirmed its inter-laboratory reproducibility and the stability over time of its expression. 21,35 We demonstrated that CD69 expression was significantly correlated with CD38, CD49d and ZAP-70 and IGHV mutational status.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…The optimal cut off for CD69 expression yielding the best separation of CLL patients into 2 subsets with significantly different prognosis was fixed at 30% of positive cells by applying the most commonly used methods. 9,13,32,34 Since our proposal is to use CD69 for prognostic purposes, we confirmed its inter-laboratory reproducibility and the stability over time of its expression. 21,35 We demonstrated that CD69 expression was significantly correlated with CD38, CD49d and ZAP-70 and IGHV mutational status.…”
Section: Discussionsupporting
confidence: 52%
“…[8][9][10][11][12] Expression of CD69 was performed by a direct 3-color immunofluorescence and this combination provided a simple flow cytometric method that could be introduced into a routine immunophenotyping panel in a clinical diagnostic laboratory. However, a standardized procedure which avoids some of the difficulties encountered with ZAP-70, and to a lesser extent with CD38, has still not been established.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, the most widely used biomarkers are cytogenetics, immunoglobulin heavy-chain variable gene mutation status (IGHV-MS) and expression of ZAP70 and CD38. [4][5][6][7][8][9][10][11][12][13][14] Despite the established prognostic value of these biomarkers, a stratification according to these parameters does not fully explain the heterogeneity of CLL. In addition, scant information is available on independent predictors of some critical events in CLL, such as clinicopathological transformation to aggressive lymphoma, also known as Richter's syndrome (RS).…”
Section: Introductionmentioning
confidence: 99%